Traﬃc congestion reduction in SUMO using reinforcement learning method - Mouly, Radia Rahman; Rini, Puja Roy; Ethic, Ahsan Habib; Ayon, Mahdi Islam (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.